Pengaruh Budaya Asing, Konsep Diri dan Pengetahuan Produk terhadap Keputusan Pembelian - Ismaliah, Devi; Surya M, Tarida Marlin (LPPM Institut Bisnis dan Informatika Kesatuan, 2019)
The purpose of this research is to find out the influence of foreign culture, self-concept and product knowledge on purchasing decisions.Based on the results of statistical tests, the regression equation shows the T-table values ​​obtained for variables in Foreign Culture, Self Concepts, Product Knowledge together affect Starbucks purchasing decisions, this can be shown by the f-value of 7.563 which is greater compared to f-table 2.70 and supported by a significance value of 0.000 which is smaller than 0.05, where the variables of Foreign Culture, Self-Concept, and Product Knowledge together have a significant effect on purchasing decisions, Hypothesis 4 is accepted.